The RNA-binding protein RNP29 is an unusual Toc159 transport substrate - Grimmer, Julia; Rödiger, Anja; Hoehenwarter, Wolfgang; Helm, Stefan; Baginsky, Sacha (Frontiers in Plant Science, 2014)
The precursors of RNP29 and Ferredoxin (Fd2) were previously identified in the cytosol of ppi2 plant cells with their N-terminal amino acid acetylated. Here, we explore whether precursor accumulation in ppi2 is characteristic for Toc159 client proteins, by characterizing the import properties of the RNP29 precursor in comparison to Fd2 and other Toc159-dependent or independent substrates. We find specific accumulation of the RNP29 precursor in ppi2 but not in wild type or ppi1 protoplasts. With the exception of Lhcb4, precursor accumulation is also detected with all other tested constructs in ppi2. However, RNP29 is clearly different from the other proteins because only precursor but almost no mature protein is detectable in protoplast extracts. Co-transformation of RNP29 with Toc159 complements its plastid import, supporting the hypothesis that RNP29 is a Toc159-dependent substrate. Exchange of the second amino acid in the RNP29 transit peptide to Glu or Asn prevents methionine excision but not N-terminal acetylation, suggesting that different N-acetyltransferases may act on chloroplast precursor proteins in vivo. All different RNP29 constructs are efficiently imported into wild type but not into ppi2 plastids, arguing for a minor impact of the N-terminal amino acid on the import process.